Keramiek : Toekomst door creativiteit. - De Schutter, Alex; Leemans, Herman; Steenhaut, Peter; Verbeke, Juliana (Wetteren : Geo Art v.z.w.)
Agneessens, Stella ; Boulaert, Mira ; Boriau, Pascal ; Caruso, Alessandro ; De Clercq, Ilse ; De Neve, Katia ; De Neys, Anja ; De Vijlder, Chris ; D'Hoe, Anja ; D'Hondt, Franky ; Huylebroeck, Tamara ; Leemans, Gunther ; Pauwels, Morena ; Reintjes, Alain ; Roels, Yoeri ; Ronsijn, Anja ; Gucht, Marina Van Der ; Van Royen, Pascal ; van Vaerenbergh, Kurt
Nederlands
boek